Behaviour of intermediate stiffness culverts with recycled concrete aggregate backfill. (September 2021) - Sohrabpour, Amir Hossein; Long, Michael
Highlights: Tests and in situ behaviour of relatively unusual geomaterial. Study of structures previously not well documented. Large sized laboratory testing. Two fully instrumented full-scale culverts. Sophisticated modelling and calibration of model parameters. Abstract: Intermediate stiffness culverts behave in a manner between that of rigid structures, where the structural stiffness dominates, and flexible culverts where the soil properties are most important. Analysis and design of intermediate stiffness culverts requires a thorough understanding of soil-structure interaction. In addition the use of recycled concrete aggregate (RCA) as a backfill material to culverts is not well studied. Here the behaviour of two fully instrumented full scale intermediate stiffness culverts, one of which was backfilled with RCA, was examined by means of a series of large scale laboratory tests, detailed in situ testing and by a series of numerical models. It was found that the RCA behaves as a competent engineering material in a manner very similar to the natural sand and gravel tested. Both materials dilate strongly on loading and exhibit strong non-linearity of stiffness. The Hardening Soil Model (HSM) constitutive relationships were found to be well suited to these materials. A combination of in situ geophysics and some measurements and modelling of locally instrumented large scale laboratory testing was required to give the necessary input parameters. Monitoring of the 6 m high arch culvert showed the structure distorted in a linear elastic manner with distortions less than 20 mm, strains induced in the structural concrete less than 700 microstrain and earth pressures close to theoretical in situ (K0 ) earth pressures. No measureable movement was observed in the 300 mm thick, 3 m high box culvert. The numerical models successfully captured the behaviour of both culverts. The work demonstrates that potential savings could be made in the development of intermediate stiffness culverts, particularly in the required thickness of the soil cover and the size of the backfill zone but possibly also in the size of the structural elements.